Self-assembly of PS-PNaSS-PS triblock copolymers from solution to the solid state. Issue 21 (9th May 2017) - Nehache, Sabrina; Semsarilar, Mona; In, Martin; Dieudonné-George, Philippe; Lai-Kee-Him, Joséphine; Bron, Patrick; Bouyer, Denis; Deratani, André; Quemener, Damien
Abstract : Morphological development of block copolymer assemblies from solution to the solid state is explored to yield nanostructured materials. Abstract : Block copolymer assemblies are fascinating objects that have been studied for years. In this work, the PS-PNaSS-PS ABA triblock copolymer was synthesized by RAFT polymerization and self-assembled in a selective medium (THF/water). Various morphologies of aggregates were identified (spheres, cylinders, and vesicles) but we focused on large compound vesicles which gave birth to porous materials after solvent evaporation. The change in solvent composition upon drying was modeled and correlated to the change in morphology observed using microscopy techniques such as AFM, TEM and cryo-TEM. The large compound vesicles were found to partially fuse to form a bulk material before the vesicular compartments were opened to yield pores of about 30 nm.